The Embodiment of Islamic Boarding School-Based School Management in Improving The Quality of Graduates - Syamsul Bahri (ETDC: Indonesian Journal of Research and Educational Review, 2023)
A national character-strengthening educational program known as "Islamic Boarding Based School" can foster various intelligences, religious spirituality, and life skills. As a result, curriculum management in Islamic boarding schools affects the caliber of graduates from those institutions. So by implementing good and integrated Islamic boarding school-based school management at MAS As'adiyah Sengkang, it will produce quality graduates. This research aims to: 1) determine how Islamic boarding school-based school management improves the quality, and 2) determine the implications of Islamic boarding school-based school management in improving the quality. A qualitative research design employing a case study methodology was employed in this study. Observation, interviews, and documentation were the methods of data gathering employed. As a consequence of the findings, MAS As'adiyah Sengkang's management is divided into four phases: 1) planning by holding work meetings at the start of the new school year; 2) organizing by providing duties proportionally and professionally; 3) mobilization carried out in the form of performance based on the work program; and 4) supervision in the form of assessments in evaluating performance by school leaders. There are two implications of the implementation of Islamic boarding school-based school management that research found at MAS As'adiyah Sengkang, namely theoretical implications that include the vision, mission, and goals of the school as well as the need to develop awareness of cooperation in improving the quality of graduates.